EXAMINapp: An Evolved Secure Anonymous Assessment Information System Using NFC And QR Technologies - Rios-Aguilar, Sergio; Morente-Molinera, Juan Antonio; Pascual-Espada, Jordán (IEEE Latin America Transactions, 2017)
Preferential treatment or even potential bias which subconsciously affect marking is an important problem in current assessment models. To date, several systems have been developed to prevent the evaluators from relating exams to the applicants, but they require specific preparations before the exam, and usually involve high cost. The presented system, EXAMINapp, makes use of NFC and QR technologies, and is designed to preserve the anonymity of the student therefore avoiding the aforementioned problems. Additionally, it reduces the time spent handing in the exams, speeds up the process of submitting marks and increases the overall efficiency of requesting exam reviews.
Keywords: anonymous assessment; mobile information system; NFC; QR; IS Management; JCR; Scopus